A bona fide purchaser for valuable consideration: a special creature under the Malaysian land law - Mohamad, Nor Asiah (2004)
Bona fide purchaser seem to have a very comfortable place under the Malaysian land law. The NLC has expressly stated that in case of any conflict of interest between bona fide purchasers and others, the bona fide purchasers shall be given priority. In tackling this issues, the writer will first provide a detail discussion on the point who are the people that fall under the category of bona fide purchaser based on case law. What are the principles or criteria used by the court in their findings. The discussion will include identifying the criteria used by the courts in classifying those persons as bona fide purchaser. Lastly the paper will also highlight the dilemmas and problems arising as a result of some court decisions in giving priority to bona fide purchasers especially under a system where registration is of a paramount consideration. This paper seeks to show that the privillage given to the so called bona fide purchasers, to a certain extent, may develop a conflict of principle under the Malaysian Torrens system.